A new inactive conformation of SARS‐CoV‐2 main protease. Issue 3 (21st February 2022) - Fornasier, Emanuele; Macchia, Maria Ludovica; Giachin, Gabriele; Sosic, Alice; Pavan, Matteo; Sturlese, Mattia; Salata, Cristiano; Moro, Stefano; Gatto, Barbara; Bellanda, Massimo; Battistutta, Roberto
Abstract : A new inactive conformation of SARS‐CoV‐2 main protease that is relevant to comprehension of the catalytic cycle and for structure‐based drug‐design approaches is reported. Abstract : The SARS‐CoV‐2 main protease (M pro ) has a pivotal role in mediating viral genome replication and transcription of the coronavirus, making it a promising target for drugs against the COVID‐19 pandemic. Here, a crystal structure is presented in which M pro adopts an inactive state that has never been observed before, called new‐inactive. It is shown that the oxyanion loop, which is involved in substrate recognition and enzymatic activity, adopts a new catalytically incompetent conformation and that many of the key interactions of the active conformation of the enzyme around the active site are lost. Solvation/desolvation energetic contributions play an important role in the transition from the inactive to the active state, with Phe140 moving from an exposed to a buried environment and Asn142 moving from a buried environment to an exposed environment. In new‐inactive M pro a new cavity is present near the S2′ subsite, and the N‐terminal and C‐terminal tails, as well as the dimeric interface, are perturbed, with partial destabilization of the dimeric assembly. This novel conformation is relevant both for comprehension of the mechanism of action of M pro within the catalytic cycle and for the successful structure‐based drug design of antiviral drugs.